Pengaruh Layanan Informasi Karir Terhadap Pemilihan Karir Siswa Kelas XI SMK Negeri 1 MandrehE - Indah Krisda Gulo; Hosianna Rodearni Damanik; Famahato Lase; Justin Foera-era Lase (Conseils : Jurnal Bimbingan dan Konseling Islam, 2025)
The aim of this research is to determine the influence of career information services on career choice. This study uses an approach positivism-quantitative.  Data collection was carried out by distributing questionnaires. The research location was carried out at SMK Negeri 1 Mandrehe. The population in this study was class XI with the research sample being class XI AKL.  The analysis technique in this research uses the T test which is carried out by comparing the difference in values mean pre test (before treatment) and value post test (after being given treatment). The results of the T test show a significance value of 0.000 ≤ 0.05, which means that career information services for career selection are classified as effective, with a value of mean pre test 62.74 while the value mean post test 99.80 with difference mean amounting to 37,333. So this research shows that career information services influence students' career choices.